2007
DOI: 10.1088/0953-8984/19/24/246208
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance in nanoparticles: between ferro- and paramagnetism

Abstract: Magnetic nanoparticles of γ-Fe 2 O 3 coated by organic molecules and suspended in liquid and solid matrices, as well as a non-diluted magnetic fluid have been studied by electron magnetic resonance (EMR) at 77-380 K. Slightly asymmetric spectra observed at room temperature become much broader, symmetric, and shift to lower fields upon cooling. An The shift and broadening of the spectrum upon cooling are ascribed to the role of the surface layer, which is considered with taking into account the strong surface-r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
86
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(98 citation statements)
references
References 46 publications
11
86
1
Order By: Relevance
“…This procedure was performed for the room temperature data, where the narrow component could be distinguished from the total signal. Then, based on the observation that the width of the narrow component does not change significantly with temperature variation, the other points in the graph of 4b were calculated using the amplitude of the derivative of the signal, similar to the procedure described in [10]. The temperature dependence of the narrow component was fitted by the Arrhenius law, ~exp(-E/k B T), and shown in the figure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This procedure was performed for the room temperature data, where the narrow component could be distinguished from the total signal. Then, based on the observation that the width of the narrow component does not change significantly with temperature variation, the other points in the graph of 4b were calculated using the amplitude of the derivative of the signal, similar to the procedure described in [10]. The temperature dependence of the narrow component was fitted by the Arrhenius law, ~exp(-E/k B T), and shown in the figure.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed description of the samples and results of EMR studies in γ-Fe 2 O 3 suspensions can be found in [10]. Note, that the bulk saturated magnetization of γ-Fe 2 O 3 (~ 400 e.m.u.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strong surface anisotropy results in an increase of the average resonance frequency of the surface spins. Due to exchange interactions, this frequency shift is partly transferred to the bulk spin system, leading to the corresponding shift of the FMR spectrum toward lower fields [19]. Fig.…”
Section: Ferromagnetic Resonancementioning
confidence: 94%
“…5, right axis) reveals that in the case of polymer sample it increases slightly on cooling from RT down to about 150 K but decreases on further cooling, especially strongly below 50 K. The apparent resonance field is slightly smaller in the nanopowder sample what can be explained by the existence of bigger internal field in that stronger magnetic material. The shift of the resonance field toward lower magnetic field could be explained by the coreshell model [19]. The core is assumed to be in the ferromagnetic (superparamagnetic) state and the surface layer in the paramagnetic state.…”
Section: Ferromagnetic Resonancementioning
confidence: 99%